A cross sectional community-based study to determine prevalence of high blood pressure and its associated risk factors amongst women residing in rural area of Navsari district in Gujarat - Vyas, Parth H.; Dhadwe, Kanchan; Shah, Harsha A.; Dave, Hiral M. (International Journal Of Community Medicine And Public Health, 2020)
Background: The increase in prevalence of hypertension is evident in urban as well as rural areas over the years from trend studies. The objectives of this study were to determine prevalence of high BP and to assess the magnitude of undiagnosed high BP cases amongst women residing in the study area. Methods: 28 Villages which are the field practice area of Gram Seva Trust Sarvjanik Hospital, Kharel were selected. Women above 25 years of age and wanted to participate in women’s health screening camps were included. Results: 31% belonged to the age group of 36 to 45 years. 49.7% among the study participants were engaged in farm labor. 25.4% women were underweight. As per the JNC–7 criteria it was found that 13.7 % and 7.4% women were in stage 1 and stage 2 respectively. 21.6% women were in the pre-hypertension stage. 82% women were newly diagnosed and didn’t know that they were hypertensive. Significant relation between high body mass index (BMI) and hypertension was found. However, the prevalence of high BP amongst underweight and normal BMI women was alarming (13.1% and 19.8% respectively). Conclusions: There is significant burden of women with high BP in rural areas in Navsari district. This invites for immediate population and high-risk approach to lower blood pressure in the community and thereby reducing the risk of cardiovascular diseases.